Physical exercise and children’s resilience: mediating roles of self-efficacy and emotional intelligence - Jiang, Caixia; Wang, Kun; Qin, Hao (Frontiers in Psychology, 2025)
PurposeThis study aims to examine the inner relationship between children’s physical exercise, self-efficacy, emotional intelligence, and resilience, and explore effective ways to promote the improvement of children’s resilience.MethodsUsing measurement tools such as the Physical Activity Rating Scale (PARS-3), the General Self-Efficacy Scale (GSES), the Chinese version of the Emotional Intelligence Scale (EIS), and the Adolescents Resilience Scale, we conducted a questionnaire survey was conducted among 700 primary school students in 4 primary schools. The SPSS 22.0 software was used to process and analyze the data, including correlation analysis, regression analysis, and Bootstrap analysis, and AMOS 21.0 software was used to establish a structural equation model.Results(1) Physical exercise has a significant positive correlation with self-efficacy (r = 0.29, p < 0.001), emotional intelligence (r = 0.32, p < 0.001), and resilience (r = 0.37, p < 0.001), and there is also a significant positive correlation between emotional intelligence and resilience (r = 0.30, p < 0.001). (2) Physical exercise can directly and positively predict children’s resilience (β1 = 0.38) and its five sub-dimensions, that is, physical exercise can positively predict goal concentration (β = 0.35, p < 0.001), emotional control (β = 0.29, p < 0.001), positive cognition (β = 0.20, p < 0.01), family support (β = 0.33, p < 0.001), interpersonal assistance (β = 0.31, p < 0.001), respectively. (3) Self-efficacy (SE = 0.10) and emotional intelligence (SE = 0.08) have partial mediating effects, respectively, on the relationship between physical exercise and resilience, and the chain mediation effect of self-efficacy and emotional intelligence also reaches a significant level (SE = 0.02).ConclusionPhysical exercise can have a positive impact on children’s resilience through self-efficacy and emotional intelligence, so schools or parents should attach importance to children’s physical activities, which is an effective way to improve their resilience.